Pengaruh Media Pembelajaran Berbasis Audio Visual Terhadap Hasil Belajar Matematika Kelas 1 SD Negeri 1 Pokak Ceper - Helga Putri Fatmawati; Lintang Perdana Ferianton; Daru Ken Mahanani; Nela Rofisian (Journal Innovation In Education, 2025)
This research focuses on examining the influence of audio-visual media on the learning outcomes of first-grade students at SD Negeri 1 Pokak Ceper, particularly in the topic of recognizing flat shapes. Using a qualitative method with a descriptive approach, the study collected data through observations and interviews conducted during the teaching-learning process. The findings reveal that incorporating audio-visual media significantly boosts students' engagement and understanding of the material. Students demonstrated increased activeness, enthusiasm, and motivation compared to traditional teaching approaches. Based on these findings, the study advocates for the adoption of audio-visual media as an effective tool in teaching mathematics to enhance the quality of education at the elementary school level..